A study on issues of foreign worker faced by project personnel in construction industry / Muhamad Azri Abdul Kadir - Abdul Kadir, Muhamad Azri (2021)
The Malaysian construction industry play important role in generating wealth to the country and development of socio economic. Even foreign workers working in Malaysia to overcome the shortage of manpower in the construction industry, more dependence on foreign workers is causing negative effects and has become a serious social problem in the country. Increasing foreign worker is expected to give good solution, but problem in foreign worker attitude create more problem to Malaysian construction companies. The aims are to study about issue of foreign worker faced by contractor in construction industry. The objective this paper is to investigate the problem and issues of foreign worker in construction industry and to identify the factors that affect contractor in employing foreign workers in construction industry. The last objective is to identify solution to minimise the issues of foreign workers Data will be collected through quantitative methods. Questionnaires will be distributed to professionals in the construction projects that have a direct relationship with foreign workers.